Konstruksi Identitas Kolektif dalam Pidato Abu Ubaidah: Analisis Intertekstual terhadap Hadis - Ahmad Bagas Prakoso (Universitas Negeri Padang, 2026)
This study examines the intertextuality of hadith in Abu Ubaidah’s speeches through Julia Kristeva’s theory of intertextuality. It aims to analyze the mechanisms of hadith reformulation and their functions in constructing religious authority and collective identity within religious discourse. This research employs a descriptive qualitative method using purposive sampling on six excerpts selected from five speeches delivered between 2023 and 2025. The findings reveal five mechanisms of hadith reformulation: direct, contextual, conceptual, legitimative, and expansive reformulation. Furthermore, hadith intertextuality functions semantically, rhetorically, and symbolically in producing meaning, strengthening persuasion, and reinforcing collective identity. The study demonstrates that hadith are strategically reformulated to establish religious legitimacy and ideological cohesion in discourse. These findings highlight that hadith intertextuality functions as a dynamic discursive instrument in shaping meaning, authority, and collective identity in contemporary religious discourse.